The War of the Ember : Guardians of Ga$1 (BHooles #15 - Lasky, Kathryn (New York : Scholastic, 2008)
When Nyra and the Striga join forces to wake the hagsfiends, powerful evil beings who have not been seen in many centuries, the Guardians form an alliance of free creatures to oppose them.
"Apple series"--P. [4] of cover.
Keywords: Owls -- Fiction; Fantasy; Owls -- Fiction; Fantasy fiction